Contribution to the taxonomy of little known Tragopogon species endemic to Turkey. (23rd July 2021) - Gültepe, Mutlu; Coşkunçelebi, Kamil; Makbul, Serdar; Güzel, Murat Erdem
Abstract : In the present paper, two little‐known species ( T. olympicus Boiss. and T. pichleri Boiss.) endemic to Turkey are evaluated in terms of morphology based on numerous authentic and/or new collections. Additionally, the phylogenetic positions of these little‐known species are evaluated based on newly generated sequences of nrDNA ITS, trn L and trn L‐F. As a result of the morphological examination, lectotypes are designated and documented for both species together with amended diagnosis. The phylogenetic analysis of the ITS data indicates that T. olympicus and T. latifolius Boiss. var. angustifolius are sister taxa, while T. dubius Scop. and T. pichleri are nested together in a different subclade of Tragopogon sect. Majores (Artemcz.) Kuthath s.l. However, neither species is resolved in the cpDNA tree due to low nucleotide diversity. The present results support treating T. olympicus and T. pichleri as members of Tragopogon sect. Sosnovskya Boriss. and Tragopogon sect. Majores, respectively.